The negative impact of HBV/HCV coinfection on cirrhosis and its consequences. Issue 11 (9th October 2017) - Pol, S.; Haour, G.; Fontaine, H.; Dorival, C.; Petrov‐Sanchez, V.; Bourliere, M.; Capeau, J.; Carrieri, P.; Larrey, D.; Larsen, C.; Marcellin, P.; Pawlostky, J.‐M.; et al.
Summary: Background: Hepatitis B virus (HBV)/hepatitis C virus (HCV) confection has been rarely studied in nonasian series. Aim: To compare the characteristics of HBV/HCV coinfected patients to those of HBV‐ or HCV‐monoinfected patients in the ANRS CO22 HEPATHER cohort study. Patients and Methods: Of the 20 936 included patients, 95 had HBV/HCV coinfection (hepatitis B surface antigen, anti‐HCV antibody and HCV RNA positive) and were matched with 375 HBV‐ and 380 HCV‐monoinfected patients on age, gender and time since HBV or HCV diagnosis. Results: F3‐F4 fibrosis was more frequent in coinfected patients (58%) than in HBV‐ (32%, P < .0001), but similar in HCV‐monoinfected patients (52%, P = .3142). Decompensated cirrhosis was more frequent in coinfected patients (11%) than in HBV‐ (2%, P = .0002) or HCV‐ (4%, P = .0275) monoinfected patients. Past excessive alcohol use was more frequent in coinfected patients (26%) than in HBV (12%, P = .0011), but similar in HCV monoinfected patients (32%, P = .2868). Coinfected patients had a higher proportion with arterial hypertension (42%) than HBV‐ (26%) or HCV‐monoinfected patients (25%) ( P < .003). Multivariable analysis confirmed the association between F3‐F4 fibrosis and HCV infection in HBV‐infected patients (OR = 3.84, 95% CI 1.99‐7.43) and the association between decompensated cirrhosis and coinfection in HBV infected (OR = 5.58, 95% CI 1.42‐22.0) or HCV infected patients (OR = 3.02, 95% CI 1.22‐7.44). Conclusions: HCV coinfection harmfully affects liver fibrosis in HBV patients, while decompensated cirrhosis is increased in coinfected patients compared with HBV‐ or HCV‐monoinfected patients. HCV treatment is as safe and effective in coinfected as monoinfected patients and should be considered following the same rules as HCV monoinfected patients. Abstract : Linked Content This article is linked to Pol et al and Huang et al papers. To view these articles visithttps://doi.org/10.1111/apt.14476 andhttps://doi.org/10.1111/apt.14445 .